The role and contributions of Indonesia's young generation through a national resilience perspective: Case study of the Nusantara capital area - Auzar, Muhammad; Ramadani, Wanda Ulfia; Saputra, Nanda (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The Capital City of Nusantara (IKN) as the new center of Indonesia's government presents challenges and opportunities for the younger generation to maintain national resilience. Methods: This type of research is qualitative research. The author presents the research with descriptive scientific analysis, referring to literature and various reliable sources. The data sources used in this paper consist of various libraries, including related books, articles, and journals relevant to the discussion of the problem. Findings: The relocation of the capital is not only a physical move, but also has an impact on social, cultural, and economic interactions, and physical movement, but also has an impact on the social, cultural, and economic interactions of the community society. Conclusion: The results showed that the younger generation plays an important role in preventing various forms of threats to national resilience with a caring attitude towards social and environmental issues. Novelty/Originality of this article: The novelty of this research lies in its focus on the relocation of Indonesia's capital city and the impact of the move. This research highlights the impact of the move from the perspective of national resilience as well as culture and the role of the younger generation in the relocation of the nation's capital.